Rapid facial mimicry in orangutan play - Davila Ross, Marina (The Royal Society, 2007)
Emotional contagion enables individuals to experience emotions of others. This important empathic phenomenon is closely linked to facial mimicry, where facial displays evoke the same facial expressions in social partners. In humans, facial mimicry can be voluntary or involuntary, whereby its latter mode can be processed as rapid as within or at 1 s. Thus far, studies have not provided evidence of rapid involuntary facial mimicry in animals. This study assessed whether rapid involuntary facial mimicry is present in orangutans (Pongo pygmaeus; N=25) for their open-mouth faces (OMFs) during everyday dyadic play. Results clearly indicated that orangutans rapidly mimicked OMFs of their playmates within or at 1 s. Our study revealed the first evidence on rapid involuntary facial mimicry in non-human mammals. This finding suggests that fundamental building blocks of positive emotional contagion and empathy that link to rapid involuntary facial mimicry in humans have homologues in non-human primates.